Organoids as Tools for Investigating Skin Aging: Mechanisms, Applications, and Insights - Xin-Yu Wang; Qian-Nan Jia; Jun Li; He-Yi Zheng (Biomolecules)
Organoids have emerged as transformative tools in biomedical research, renowned for their ability to replicate the complexity construct of human tissues. Skin aging is a multifaceted biological process, influenced by both intrinsic factors and extrinsic factors. Traditional models for studying skin aging often fall short in capturing the intricate dynamics of human skin. In contrast, skin organoids offer a more physiologically relevant system, reflecting the structural and functional characteristics of native skin. These characteristics make skin organoids highly suitable for studying the mechanisms of skin aging, identifying novel therapeutic targets, and testing anti-aging interventions. Despite their promise, challenges such as limited scalability, reproducibility, and ethical considerations remain. Addressing these hurdles through interdisciplinary research and technological advancements will be essential to maximizing the potential of skin organoids for dermatological research and personalized anti-aging therapies.